On the dynamics of a modified Lorenz-Stenflo system - Rech P.C.* (2020)
© 2020 World Scientific Publishing Company.The Lorenz-Stenflo system is a four-parameter four-dimensional autonomous nonlinear continuous-time dynamical system, derived to model the time evolution of finite amplitude acoustic gravity waves in a rotating atmosphere. In this paper, we propose a modified Lorenz-Stenflo system, where the variable x in the fourth equation of the original Lorenz-Stenflo system was replaced by ln|x|. We investigate cross-sections of the parameter-space of this new system, characterizing regions of different dynamical behaviors. We show that the aforementioned replacement may promote the emergence of organized periodic structures in places of these cross-sections, where they did not exist before modification.